2021
DOI: 10.1177/17455065211063279
|View full text |Cite
|
Sign up to set email alerts
|

Level and determinants of long-acting family planning utilization among reproductive age women in Harar, Eastern Ethiopia

Abstract: Background: Ethiopia’s population is currently estimated to be 117,814,659 people and continues to have countries with the highest maternal mortality rates. Family planning is one of the most effective techniques for lowering mother and child mortality, in addition to limiting rapid population expansion. Objective: The aim of this study was to assess level and determinants of long-acting family planning method among reproductive age women in Harar, Eastern Ethiopia, 2021 Method: Community-based cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…This variation is reflected not only in various part of the country but is seen globally. Uptake in Ghana (70%), 17 Gambia (88.7%) 18 and ACOG among American 75% 17 but lower rates were obtained in Malawi (2%), 19 Ethiopia(29%), Kenya (20.6) 6 Indonesia (10.66%) 9 ,Australia(11%) among contraceptive users4. Several factors have been shown to mitigate the utilization of LARCs such as age, education, family income, cost of contraception, , knowledge, woman beliefs, attitude, , availability, contraceptive-related skills, provider bias, support from partners, friends,, and also support from leaders in the community, access to quality services 10,16,17,18,20,22 Among the LARCs, some studies agree that IUCD was the most used, closely followed by implants 4,16,23,24 which is similar to the finding in this study, The study revealed that equal number of women IUCD users used implants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This variation is reflected not only in various part of the country but is seen globally. Uptake in Ghana (70%), 17 Gambia (88.7%) 18 and ACOG among American 75% 17 but lower rates were obtained in Malawi (2%), 19 Ethiopia(29%), Kenya (20.6) 6 Indonesia (10.66%) 9 ,Australia(11%) among contraceptive users4. Several factors have been shown to mitigate the utilization of LARCs such as age, education, family income, cost of contraception, , knowledge, woman beliefs, attitude, , availability, contraceptive-related skills, provider bias, support from partners, friends,, and also support from leaders in the community, access to quality services 10,16,17,18,20,22 Among the LARCs, some studies agree that IUCD was the most used, closely followed by implants 4,16,23,24 which is similar to the finding in this study, The study revealed that equal number of women IUCD users used implants.…”
Section: Discussionmentioning
confidence: 99%
“…Developing regions account for approximately 99% (302 000) of global maternal deaths in 2015, with sub-Saharan Africa alone accounting for roughly 66% (201 000), followed by Southern Asia (66 000). 9 In most Sub Saharan countries the maternal mortality ratio is about 415 -maternal deaths per 100,000 live births, that is more than 40 times higher than that of most of the European countries, and almost 60 times higher than in Australia and New Zealand. 10,11 Family planning is one of the intervention tools in achieving the SDG target 3.1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Family planning refers to a consideration of the number of children a person wishes to have, including a choice to have no children, at the age at which they wish to have them [1,2]. Worldwide, the maternal mortality ratio remains high, at 287 maternal deaths per 100,000 births; a large proportion of these deaths occur among young women [2,3].…”
Section: Introductionmentioning
confidence: 99%